Governance Design of School Information Systems With the Open Group Architecture Framework (TOGAF) AT 1st State High School Pagelaran - Noca Yolanda Sari; Leni Anggraeni (Institut Bakti Nusantara, 2022)
The 1st State High School Pagelaran is one of the best public schools in Pringsewu Regency. This school is also an excellent state school where many of its students achieve achievements in both academic and non-academic fields. Currently, the 1st State High School Pagelaran does not yet have specific and integrated school information system architecture. Therefore, school information system architecture is needed that is in accordance with the needs in the framework of the information system development process at the 1st State High School Pagelaran. An organization in improving the performance of every business process that takes place in it must utilize information technology and information systems. However, this school does not yet have an integrated information system. Therefore, it is necessary to design an enterprise architecture that is used as a reference for the construction and development of school information systems. Enterprise Architecture Is the process of translating the vision and strategy of a business into more effective change. This study discusses the design of School Information System Architecture at the 1st State High School Pagelaran using TOGAF (The Open Group Architecture Framework) with the Architecture Development Method (ADM). The stages used in this architectural design are Architecture Vision, Business Architecture, Application Architecture, and Technology Architecture. The results of this research are the design of information systems and the design of the School Information System Architecture by producing a model and a basic framework called a BluePrint or Enterprise Architecture Model that can be used to design and develop information systems.